First record of tapeworm Moniezia (Cestoda: Anoplocephalidae) infections in Leopards: Coprological survey of gastrointestinal parasites of wild and captive cats in Sri Lanka - Vishvapali Kobbekaduwa; Caroline Fillieux; Ashan Thududgala; R.P.V. Jayantha Rajapakse; Rupika Subashini Rajakaruna (Journal of Threatened Taxa, 2017)
Sri Lanka is home to four species of wildcats: Leopard, Fishing Cat, Rusty-spotted Cat and Jungle Cat.  All four, except the Jungle Cat, are listed threatened.  A coprological survey was carried out in 2014 to determine the gastrointestinal (GI) parasites of wild and captive cats in Sri Lanka.  Parasite eggs and cysts were isolated and morphologically identified using iodine smears and a modified salt flotation.  The intensity of infection was quantified using a McMaster counting technique.  A total of 45 fecal samples were analyzed.  Except for the six captive Rusty-spotted Cats, all cats were infected with one or more GI parasites.  The presence of Moniezia sp. in Leopards in the Horton Plains National Park with an intensity of 150–1850 EPG (eggs per gram of feces) was unexpected.  Moniezia is a common GI parasite of ruminants and before our study it had never been recorded in Leopards.  Cross species infection with Moniezia could be possible due to accidental ingestion of cysticercoid infected oribatid mites, the intermediate host which could have been picked up in the pasture while feeding on carcasses.  Among the other parasitic infections in Leopards Toxocara was most common (61.9%) followed by strongyle infections (15.4%).  Of the fecal samples collected from wild Leopards 80.0% were infected with GI parasites while no GI parasites were found in the captive Leopard samples.  The Jungle Cats and the Rusty-spotted Cats sampled were in captivity and only the Jungle Cats were infected with strongyles.  Toxocara was recorded in Leopards and Fishing Cat both in captivity and in the wild.  It is a common GI infection of cats causing morbidity in all age groups and mortality in young animals.  Although parasitic infections of cats may not be a direct reason for a species’ decline, parasitic infections spreading within a small fragmented population could reduce the vitality and numbers and threaten the population further.  This is the first report of GI parasites of wildcats of Sri Lanka and the first record of Moniezia infections in Leopards.